Analisis Pola Perubahan Perilaku dalam Gaya Hidup Konsumtif Keluarga PMI: Literatur Review - Khumairoh, Melisa; Arif, Muhamad Ridwan; Al Farizi, M Salman; Mufida, Widia Hilmi (Sociocouns: Journal of Islamic Guidance and Counseling, 2025)
This study aims to analyze the pattern of changes in consumptive lifestyle behavior in the families of Indonesian Migrant Workers (PMI) based on literature published in the last 5 years. Using the literature study method, this research critically reviews 10 academic journals that discuss socio-economic changes in PMI families. The results show that the increase in income from PMI remittances significantly changes their families' consumption patterns and lifestyles. These changes include increased spending on non-essential items, a shift in priorities from long-term investment to short-term consumption, and a tendency to use materials as symbols of social status. The consequences of these changes include manifest functions such as increased comfort and confidence, as well as latent functions such as wasteful behavior, social jealousy, and potential family conflict. In conclusion, although PMI remittances improve economic welfare, they also encourage changes in consumptive behavior that can have a negative impact on the social dynamics and long-term welfare of PMI families.